Isolation and Characterization of Lactic Acid Bacteria Isolates from Traditional Sambas Pekasam Based on Lundu Fish and Milkfish - Maherawati; Simamora, Cico Jhon Karunia (BIOEDUSCIENCE, 2025)
Background: Pekasam, or Bekasam, is a fermented fish product that can potentially produce lactic acid bacteria (LAB). This study aims to isolate and characterize LAB from Pekasam from Sambas Regency. TPC results on MRS media showed that Pekasam from Sambas Regency can potentially contain LAB with a total colony of 107 CFU/g. The isolates were identified for their colony and cell shape so that three selected isolates were obtained, namely SB1(1), SB3(1), and SB3. Methods: Isolates were characterized for proteolytic activity, hemolytic activity, low pH tolerance, tolerance to the presence of bile salts, carbohydrate metabolism, and potential antimicrobial activity. All isolates had round colonies, convex or raised surfaces, flat edges, milky white, rod-shaped cells, and were classified as gram-positive bacteria. Results: All isolates showed proteolytic activity, ɤ-hemolysis, had low pH tolerance with viability <60% at pH 2 and 3, were resistant to bile salts with viability <73% at NaDC concentrations of 0.2 and 0.4 mmol, were able to metabolize carbohydrates and had antimicrobial activity. The selected isolates were identified as Lactobacillus species and were homofermentative. Conclusion: The three selected isolates can potentially be homofermentative LAB of Lactobacillus species.